2014
DOI: 10.1111/1478-9302.12036
|View full text |Cite
|
Sign up to set email alerts
|

What was Progressive in ‘Progressive Conservatism’?

Abstract: In January 2009 David Cameron announced that the ‘underlying philosophy’ of his government would be progressive conservatism. Despite the ambiguity about this term, it was generally interpreted as a signal that Cameron was moving his party to the left. To some commentators, Cameron was allying with the progressive ‘one nation’ strand of conservative thought. To others, particularly in the media, he was drawing on the more immediate influence of Phillip Blond's ‘Red Toryism’. However, the focus on the market (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Following David Cameron's election as leader, a series of initiatives suggested that he was seeking to introduce new thinking to the Party, and to align it with interests and issues that it had not been linked with since at least the start of the Thatcher period (McAnulla, 2010;Page, 2010;Bochel, 2011;Griffiths, 2014;Kerr and Hayton, 2015). For example, in speeches Cameron appeared to make the case for a new approach, including to poverty (2006c) and anti-social behaviour (2006b), and highlighted a commitment to the NHS (2006a); he created six policy review groups, only one of which was directly concerned with economic matters, while one focused on social justice, chaired by Iain Duncan Smith; and in January 2009 he launched the idea of 'progressive Conservatism' at the Demos think tank, talking about using Conservative means to achieve 'progressive ends', such as a fairer, more equal and safer society (for example, Robinson and Twyman, 2014).…”
Section: The Strange Re-emergence Of Compassionate Conservatismmentioning
confidence: 99%
See 2 more Smart Citations
“…Following David Cameron's election as leader, a series of initiatives suggested that he was seeking to introduce new thinking to the Party, and to align it with interests and issues that it had not been linked with since at least the start of the Thatcher period (McAnulla, 2010;Page, 2010;Bochel, 2011;Griffiths, 2014;Kerr and Hayton, 2015). For example, in speeches Cameron appeared to make the case for a new approach, including to poverty (2006c) and anti-social behaviour (2006b), and highlighted a commitment to the NHS (2006a); he created six policy review groups, only one of which was directly concerned with economic matters, while one focused on social justice, chaired by Iain Duncan Smith; and in January 2009 he launched the idea of 'progressive Conservatism' at the Demos think tank, talking about using Conservative means to achieve 'progressive ends', such as a fairer, more equal and safer society (for example, Robinson and Twyman, 2014).…”
Section: The Strange Re-emergence Of Compassionate Conservatismmentioning
confidence: 99%
“…Cameron and his fellow modernisers arguably pursued a twin track approach, attempting to distance themselves from their predecessors and to challenge the perception of the Conservatives as the 'nasty party', while still appealing to traditional Conservative supporters (see, for example, McAnulla, 2010;Buckler and Dolowitz, 2012;Griffiths, 2014), so that while talking about tackling poverty, supporting the NHS and climate change, they were also promoting long-standing Conservative views on subjects such as crime, family structures and personal freedom, and taking responsibility away from the state and giving it to individuals , families and communities. Even before dropping the commitment to match Labour's public expenditure plans, they saw limited government and lower taxes as part of the solution.…”
Section: The Strange Re-emergence Of Compassionate Conservatismmentioning
confidence: 99%
See 1 more Smart Citation
“…With other gay rights legislation such as the Sexual Offences Act 1967; the Sexual Offences (Amendment) Act 2000; the Adoption and Children Act 2002; and the Civil Partnership Act 2004, we see a number of Conservative MPs speaking in favour of progressive legislation. It is of interest, therefore, to examine how a Conservative strain of thought has encompassed issues of gay rights, and how members of the party are able to advocate progressive positions from within an anti-progressive institutional framework – (the meaning of progressivism, like so many political words, is contested: here I take Griffith’s (2014: 29) understanding that progressivism is a set of policies that is guided by optimism, is accepting of rupture, and seeks social justice. )…”
Section: Introductionmentioning
confidence: 99%
“…Eliding ‘progressive’ with ‘conservatism’ is, as Griffiths (2014: 29) has pointed out, oxymoronic, given that conservatism as a political philosophy is suspicious of change, particularly change driven by abstract reasoning built on notions such as progress. Nevertheless, ‘progressive conservatism’ is a moniker that David Cameron has chosen to use to describe his political philosophy on a number of occasions, both as the leader of the opposition and as prime minister.…”
mentioning
confidence: 99%